Cholestasis secondary to anabolic steroid use in young men. (2nd February 2012) - Elsharkawy, Ahmed M; McPherson, Stuart; Masson, Steven; Burt, Alastair D; Dawson, Robert T; Hudson, Mark
Abstract : Ask about use of anabolic steroids in young men with unexplained cholestasis to prevent progressive liver injury